2022
DOI: 10.1108/jcom-02-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational authenticity in LGBTQ communication: the scale development and initial empirical findings

Abstract: PurposeThe purpose of this study is to develop an integrative concept of perceived authenticity that captures a more nuanced perception of authenticity among LGBTQ stakeholders and to examine the effects of perceived organizational authenticity on Pride campaign evaluations.Design/methodology/approachWith 400 LGBTQ/non-LGBTQ participants, we developed a perceived organizational authenticity (POA) scale - adapted from marketing literature - adding representativeness as the fifth dimension to the context of LGBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…To answer RQ2, the social media sample and further online discourses surrounding the companies, such as interviews, the company websites, news articles, and YouTube videos, were analyzed using the dimensions of POA (Lim et al, 2022)−23 sources for Tell Me Why and eight for Bugsnax. Here, the goal is to compare organizational practices with their strategic communication, to see if they are sincerely aligning with their LGBTQ+ stakeholders, engaging in real CSR, or participating in rainbow washing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To answer RQ2, the social media sample and further online discourses surrounding the companies, such as interviews, the company websites, news articles, and YouTube videos, were analyzed using the dimensions of POA (Lim et al, 2022)−23 sources for Tell Me Why and eight for Bugsnax. Here, the goal is to compare organizational practices with their strategic communication, to see if they are sincerely aligning with their LGBTQ+ stakeholders, engaging in real CSR, or participating in rainbow washing.…”
Section: Methodsmentioning
confidence: 99%
“…If authenticity is not achieved in the eyes of queer stakeholders, i.e., communication is not consistent with organizational practices, the relationship will be compromised. Research on CSR and rainbow washing has shown that only consistent and authentic support messages positively affect the organization-stakeholder relationship (Ciszek and Pounders, 2020;Lim et al, 2022). Hence, for our research, we have formulated the following research questions:…”
Section: (In)visibility: Video Games and Lgbtq+ Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 90% of brands that promote diversity, only 4% are perceived as diverse, which questions the authenticity of Tokenism in the workplace corporate stances on DE&I, and thus LGBTQþ issues (Aird, 2019). The greater the perceived authenticity of an organization's LGBTQþ support, the lower the skepticism (Lim et al, 2022). Firms' motives for CSR are perceived as altruistic (other-serving) or egoistic (self-serving), aimed at increasing profit and own welfare (Handelman and Arnold, 1999).…”
Section: 4mentioning
confidence: 99%